Evaluation of the Success of Curriculum Modification in Indonesia in Addressing Educational Challenges for Children with Disabilities - Naurasari, Putri aisyah; Hendriani, Wiwin (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
The prevalence of children with disabilities in Indonesia is very high. According to the Central Statistics Agency (BPS), the number of children with disabilities reached 1.6 million in 2018 and increased to 22.5 million in 2020. These children require an appropriate educational approach, but the implementation of inclusive education still faces challenges. This study evaluates the implementation of inclusive education and the factors influencing the success of curriculum modification interventions. Using a literature review method, 65 articles were identified, and 10 articles met the inclusion criteria and were evaluated. The results show some successes in inclusive education but also challenges such as government preparedness, educational institutions, inadequate regulations, and insufficient infrastructure. The success of curriculum modification interventions depends on teachers' understanding of children's needs and support from the government and society. Inclusive education requires serious and collaborative efforts, including the expansion of government regulations, improvement of human resource management, and partnerships with external stakeholders. An adaptive curriculum model could be an innovative solution to better meet the learning needs of children with disabilities.